Functional Materials through Surfaces and Interfaces. (26th April 2018) - Chang, Boyce; Martin, Andrew; Gregory, Paul; Kundu, Souvik; Du, Chuanshen; Orondo, Millicent; Thuo, Martin
ABSTRACT: In most materials, surfaces and interfaces present a significant portion of the workable area, but this area has often been erroneously perceived as a challenge in processing and thus, largely ignored. Surfaces and interfaces, however, present a network of energetically mismatched (sometimes metastable) molecules that can be exploited to either control surface reactions, engineer bulk stability or reveal new fundamental details of otherwise not well understood processes or systems as described herein. This perspective captures the role of i) structure, ii) chemistry and iii) thermodynamics at the interface in fabricating functional materials. Engineering substrate morphology enables tunable wettability either through the substrate or an adsorbed self-assembled monolayer (SAM), the latter being largely due to effect of sub-nanoscale roughness on conformational defects and overall order in the SAM. Surface roughness and chemistry also dictates the nature and amount of adventitious contaminants on a surface, and this was used to control volume of adsorbed water leading to controlled and tunable step-growth polymerization. The chemical treatment renders the paper amphiphobic, which could be used for self-cleaning surfaces and nucleation of water microdroplets for water harvesting. Finally, creating a self-passivating polished thin (∼0.7-2 nm) shell on a molten metal microdroplet kinetically frustrates solidification leading to significant undercooling. The ambient undercooled liquid metal is used for mechanically-triggered heat-free solder and smart composites. These three cases demonstrate key aspects of surface and interface engineering in integrating well-known concepts for the development of functional materials.